Issues in which the Kosovan Family Law Violated Islamic Jurisprudence in the Matter of Marriage - Gashi, Bejtullah Ismail (Journal of Islamic Sciences, 2021)
This research aims to clarify the provisions in which the Kosovan family law violated Islamic Shari’a، the researcher followed the inductive method، the analytical method and the comparative method for its suitability to the study، the researcher reached a number of results، most notably that the Kosovan family law violated the Islamic Shari، a in the folloving issues: prohibiting polygamy, alloving the Muslim woman to marry a non- Muslim, the Kosovan law also allowed the court to allow to marry Non –Marriageable female relatives by affinity for acceptable and clear reasons, the researcher also recommended that the Kosovar legislator shall adopt the provisions of Islamic Shari,a that contribute to protecting the rights of family members from Islamic Sharia.
Keywords: Kosovan Law; Marriage of a Muslim to a non; Muslim; Polygyny; Non- Marriageable female relatives by affinity